(3cJGH GdMceI GdOQjI hGdOdGdI GdfhQjIs - (3CMeO Hf SdjeGf Hf eMeO Hf GdeWgQ Hf Ydj Hf GdfGUQ CMeO GdeJhcd Ydj Gddg,J (B566 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd Ndbg Edi eYQaJg OdjdkG , hde jLYd Shi UfYg Edi eYQaJg SHjdkG hHYO aEfi fXQJ ai aSGO GdYUQ hCgdg , heG XgQ ajg ef GdaSGO GdPi de jYQa eKdg ef bHdg s
(3BNQgG (B:s
(3hfSCd Gddg Cf jQaY Yf GdCeI GdShA hCf jYjPfG ef GdTjWGf hMSHfG Gddg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ GdahGJM HGdSejc HBNQgG fbd ef cdGe Ydi Hf CHj WGdH ai fgL GdHdGZI s
(3Ydi WQJgG Jedc HGSe eWgQ Hf ESeGYjd Hf YHO GdQMef heMeO Hf ESeGYjd s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs